Dark horse target Claudin18.2 opens new battlefield for pancreatic cancer - Xu, Qian; Jia, Caiyan; Ou, Yan; Zeng, Chuanxiu; Jia, Yingjie (Frontiers in Oncology, 2024)
Pancreatic cancer is one of the deadliest malignant tumors, which is a serious threat to human health and life, and it is expected that pancreatic cancer may be the second leading cause of cancer death in developed countries by 2030. Claudin18.2 is a tight junction protein expressed in normal gastric mucosal tissues, which is involved in the formation of tight junctions between cells and affects the permeability of paracellular cells. Claudin18.2 is highly expressed in pancreatic cancer and is associated with the initiation, progression, metastasis and prognosis of cancer, so it is considered a potential therapeutic target. Up to now, a number of clinical trials for Claudin18.2 are underway, including solid tumors such as pancreatic cancers and gastric cancers, and the results of these trials have not yet been officially announced. This manuscript briefly describes the Claudia protein, the dual roles of Cluadin18 in cancers, and summarizes the ongoing clinical trials targeting Claudin18.2 with a view to integrating the research progress of Claudin18.2 targeted therapy. In addition, this manuscript introduces the clinical research progress of Claudin18.2 positive pancreatic cancer, including monoclonal antibodies, bispecific antibodies, antibody-drug conjugates, CAR-T cell therapy, and hope to provide feasible ideas for the clinical treatment of Claudin18.2 positive pancreatic cancer.